Temporal patterns, spatial risks, and characteristics of tegumentary leishmaniasis in Brazil in the first twenty years of the 21st Century. - Vinícius Silva Belo; Fábio Raphael Pascoti Bruhn; David Soeiro Barbosa; Daniel Cardoso Portela Câmara; Taynãna César Simões; Lia Puppim Buzanovsky; Anna Gabryela Sousa Duarte; Saulo Nascimento de Melo; Diogo Tavares Cardoso; Lucas Edel Donato; Ana Nilce Silveira Maia-Elkhoury; Guilherme Loureiro Werneck (Public Library of Science (PLoS), 2023)
Background Tegumentary leishmaniasis (TL) is a significant public health issue in Brazil. The present ecological study describes the clinical and epidemiological characteristics of TL cases reported in the country, and analyzes the spatial and temporal patterns of the incidences and risks of occurrence across the five geopolitical regions and 27 federative units. Methodology/principal findings Data regarding new cases of TL notified between 2001 and 2020 were obtained from the Information System for Notifiable Diseases of the Brazilian Ministry of Health. Joinpoint and spatial and temporal generalized additive models were used to establish trends in the evolution of TL during the target period. The incidence rate for the entire period was 226.41 cases/100,000 inhabitants. All regions of Brazil showed trends of decreasing incidence rates, albeit with fluctuations at specific times, with the exception of the Southeast where rates have increased since 2014, most particularly in Minas Gerais state. The disease was concentrated predominantly in the North region, with Acre state leading the incidence rank in the whole country, followed by Mato Grosso (Midwest), Maranhão and Bahia (Northeast) states. The spatial distribution of the risk of TL occurrence in relation to the annual averages was relatively stable throughout the period. The cutaneous form of TL was predominant and cases most frequently occurred in rural areas and among men of working age. The ages of individuals contracting TL tended to increase during the time series. Finally, the proportion of confirmations by laboratory tests was lower in the Northeast. Conclusion/significance TL shows a declining trend in Brazil, but its widespread occurrence and the presence of areas with increasing incidence rates demonstrate the persistent relevance of this disease and the need for constant monitoring. Our findings reinforce the importance of temporal and spatial tools in epidemiologic surveillance routines and are valuable for targeting preventive and control actions.